1982
DOI: 10.1161/01.hyp.4.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensinogen in blood pressure homeostasis.

Abstract: SUMMARY The role of angiotensinogen ID blood pressure control was assessed in nonnotensive rate by observing the changes resulting from inhibition by specific rat angiotensinogen antiserum. The antiserura decreased blood pressure in rats on normal sodium as well as sodium-free diets (respectively ABP = -3 0 ± 6 mm Hg and -42 ± 8 mm Hg). In binephrectomlzed sodium-replete rats, administration of antiserum did not reduce blood pressure, whereas in sodium-depleted animals it slightly decreased blood pressure by 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…Several early studies showing a positive correlation of plasma AGT levels with blood pressure, 44 decreased blood pressure with administration of anti-AGT antibodies, 45 increased blood pressure with injection of AGT, 46 and elevated blood pressure in animals with AGT transgenes 47 offered compelling evidence linking AGT to hypertension. However, the most compelling early genetic evidence implicating this gene in essential hypertension in humans came from the study of Jeunemaitre et al 5 showing linkage between a marker downstream of the AGT gene and hypertension in affected sibships of Northern and Western European descent.…”
Section: A Genetic Link Between Hypertension and Agt?mentioning
confidence: 99%
“…Several early studies showing a positive correlation of plasma AGT levels with blood pressure, 44 decreased blood pressure with administration of anti-AGT antibodies, 45 increased blood pressure with injection of AGT, 46 and elevated blood pressure in animals with AGT transgenes 47 offered compelling evidence linking AGT to hypertension. However, the most compelling early genetic evidence implicating this gene in essential hypertension in humans came from the study of Jeunemaitre et al 5 showing linkage between a marker downstream of the AGT gene and hypertension in affected sibships of Northern and Western European descent.…”
Section: A Genetic Link Between Hypertension and Agt?mentioning
confidence: 99%
“…10,11 Injection of angiotensinogen increases blood pressure, 12 whereas antibodies against angiotensinogen decrease blood pressure. 13 Hypertensive persons with the TT genotype compared with the MM genotype at M235T had higher systolic and diastolic blood pressure and plasma angiotensinogen levels, and they were 1.6 times more likely to use an antihypertensive medication and 2.1 times more likely to use 2 antihypertensive medications. 14 In addition to the genetic evidence from the above studies, it has been suggested that the angiotensinogen gene influences the salt sensitivity of blood pressure.…”
mentioning
confidence: 96%
“…Thus, this revised concept predicts that plasma levels of angiotensin largely represent a spillover from the tissue sites of production (15). That plasma angiotensins predominantly result from the action of kidney-derived renin on plasma (liver-derived) angiotensinogen is shown by the fall in plasma angiotensin levels that follows nephrectomy (16)(17)(18)(19), and by the hypotensive effect of anti-angiotensinogen antibodies when injected into either sodium-replete or sodium-deplete rats (20). Given this local production ofAl and All by the circulating RAS, it is apparent that such local production may be subject to tissue-specific mechanisms of regulation, which cause changes in local All concentration that are not reflected in the plasma concentrations of renin or All.…”
mentioning
confidence: 99%